Hubungan Antara Konsep Diri Dengan Gaya Hidup Hedonis Pada Siswa SMA Negeri 4 Surakarta - Pontania, Almira (2016)
Hedonic lifestyle is a person's way of life that is being implemented in behaviour that prioritise indulgence and pleasure as the main purposes of life. One of the factors that influence hedonic lifestyle is self-concept. The purpose of this research is to find the relationship between self-concept and hedonic lifestyle, the level of self-concept, the level of hedonic lifestyle, and the effective contribution of self-concept towards hedonic lifestyle. The proposed hypothesis is that there is a negative relationship between self-concept and hedonic lifestyle. The subject on this research is the students of SMA Negeri 4 Surakarta which consisted of 106 students consisting of 4 classes, class XI science 3, class X science 4, class X science 5, and class XII social 1 using clusters random sampling technique. This research is using a scale of self-concept and a scale of hedonic lifestyle. The method of analysis that used in this research was product moment with software SPSS (Statistical Product and Service Solution) 16 for Windows Program. Based on the results of the analysis data shows correlation coefficient -0,469 with p value = 0.000 < 0.01 which means that there is a highly significant negative correlation between self-concept and hedonic. Based on the results of the analysis the variable of self-concept has rerata empirical (RE) equal to 71,51 and rerata hypothetic (RH) equal to 60 which means the self-concept of the students are high. While the variable hedonic lifestyle has rerata empirical (RE) equal to 52,80 and rerata hypothetic (RH) equal to 67,50 which means the hedonic lifestyle of the students are low. The effective contribution of self-concept towards hedonic lifestyle is 22% . Kata kunci : hedonic lifestyle, self-concept